2019
DOI: 10.1101/648378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MBOAT7-Driven Phosphatidylinositol Remodeling Promotes the Progression of Clear Cell Renal Carcinoma

Abstract: The most common kidney cancer, clear cell Renal Cell Carcinoma (ccRCC) is closely associated with obesity. In fact, the "clear cell" variant of RCC is given this name due to large lipid droplets within the tumor cells. Although it is well appreciated that renal lipid metabolism is altered in ccRCC, the mechanisms driving this are not well understood. Leveraging a shotgun lipidomics approach we have identified a lipid signature for ccRCC that includes an increase in arachidonic acid-enriched phosphatidylinosito… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…To characterize the lipid landscape of the HFD-versus chow-fed brain and tumor, we employed a mass spectrometry-based shotgun lipidomic analysis method that enables identification of multiple structurally distinct lipid species. This method, which we adopted without alteration, was originally published by Gromovsky et al (58) and later optimized by Neumann et al (59).…”
Section: Untargeted Mass Spectrometry-based Lipidomic Analysismentioning
confidence: 99%
“…To characterize the lipid landscape of the HFD-versus chow-fed brain and tumor, we employed a mass spectrometry-based shotgun lipidomic analysis method that enables identification of multiple structurally distinct lipid species. This method, which we adopted without alteration, was originally published by Gromovsky et al (58) and later optimized by Neumann et al (59).…”
Section: Untargeted Mass Spectrometry-based Lipidomic Analysismentioning
confidence: 99%
“…Heinrichs found that MBOAT7 might contribute to GC susceptibility through in ammation [28]. MBOAT7 was overexpressed in renal cancer cell and high MBOAT7 expression was associated with poor prognosis in ccRCC [29].CCDC58 may play a tumor-promoting role in endometrial cancer. Aldo-keto reductase 1 member B1 (AKR1B1) could be involved in various signaling pathways, such as epithelial to mesenchymal transition (EMT) [30], in ammatory responses [31], and mTOR pathway [32].…”
Section: Discussionmentioning
confidence: 99%
“…Trastuzumab and panitumab can reduce the expression of Syndecan-4, thus inhibiting tumor development and development; and After zoledronate treatment, tumor growth and migration were inhibited, but Syndecan-4 expression was increased, Therefore, the role of Syndecan-4 needs further researchs. 40 Neumann et al 41 identified a key new lipid metabolic dependence in ccRCC, and indicated that inhibition of membrane phosphatidylinositol (PI) lipid remodeling driven by membrane bound O-acyltransferase domain containing 7 (MBOAT7) might have therapeutic potential for patients with ccRCC. This follows that therapies targeting the ECM are feasible.…”
Section: Targeting the Extracellular Matrixmentioning
confidence: 99%